1972
DOI: 10.1111/j.1365-2222.1972.tb01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific sensitivity to individual grass pollens in some hay fever patients

Abstract: It has been shown in a series of 338 hay fever sufferers that about 19% give one or more (up to nine) negative skin test reactions when tested by the prick test technique to extracts of the pollens of twelve of the most widespread British grasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is easy to obtain potent extracts., and patients sensitive to other trees appear also to have IgE antibodies against birch with a high frequency (Zetterstrom, Fagerberg & Wide, 1972). Allergen extracts of various grasses cross-react in a similar manner (Milner & Tees, 1972;Berglund & Lundkvist, 1973), and timothy was chosen as a representative for the grasses present in Sweden. Food allergens were included in the panel due to their itnportance for children.…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to obtain potent extracts., and patients sensitive to other trees appear also to have IgE antibodies against birch with a high frequency (Zetterstrom, Fagerberg & Wide, 1972). Allergen extracts of various grasses cross-react in a similar manner (Milner & Tees, 1972;Berglund & Lundkvist, 1973), and timothy was chosen as a representative for the grasses present in Sweden. Food allergens were included in the panel due to their itnportance for children.…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that most grass pollens have a number of common antigens (Milner & Tees, 1972). Lowenstein (1978) showed that immunological partial identity exists between the antigen of timothy and those of cocksfoot, rye and false-oat grass pollens.…”
Section: Introductionmentioning
confidence: 99%